KURO-ARAK MONUMENTS NORTH-EASTERN AZERBAIJAN: ISSUES OF HISTORICAL, CULTURAL AND CHRONOLOGICAL INTERPRETATION (based on the materials of archaeological exploration 2001-2002. on the International project IPARC). - Kol, Filip Lantri; Magomedov, Rabadan Gadzievic (History, Archeology and Ethnography of the Caucasus, 2021)
The article is devoted to the results of exploratory archaeological research in 2001-2002. in North-East Azerbaijan, incl. Khachmass-Cuban zone, within the framework of the IPARC project (The International Program for Anthropological Research in the Caucasus; project leader - Professor Wellesley College, USA F.L.Cole). Along with the study of the medieval Gilgilchay defensive system, an international expedition, in which Azerbaijani, Dagestani and American scientists participated, conducted an exploratory survey of 15 famous settlements of the Early Bronze Age. At one of the sites (Serkertepe), a deep exploration pit was laid, which gave a fundamentally new archaeological material. The first part of the article deals with the issues of the historiography of the archaeological study of this region of Azerbaijan, adjacent to Dagestan; provides an overview of exploration and monitoring of known Kuro-Arak settlements; outlines the prospects for their further scientific study. In the second part of the article, much attention will be paid to the characterization and analysis of the materials of the exploration pit at Serkertepe, and also a new concept of the historical, cultural and chronological interpretation of the Kuro-Arak monuments of Northeastern Azerbaijan in the framework of the Great Archaeological culture will be proposed.